Involvement of leucocyte/endothelial cell interactions in anorexia nervosa. (1st June 2015) - Víctor, Víctor M.; Rovira‐Llopis, Susana; Saiz‐Alarcón, Vanessa; Sangüesa, Maria C.; Rojo‐Bofill, Luis; Bañuls, Celia; de Pablo, Carmen; Álvarez, Ángeles; Rojo, Luis; Rocha, Milagros; Hernández‐Mijares, Antonio
Abstract Background Anorexia nervosa is a common psychiatric disorder in adolescence and is related to cardiovascular complications. Our aim was to study the effect of anorexia nervosa on metabolic parameters, leucocyte–endothelium interactions, adhesion molecules and proinflammatory cytokines. Materials and Methods This multicentre, cross‐sectional, case–control study employed a population of 24 anorexic female patients and 36 controls. We evaluated anthropometric and metabolic parameters, interactions between leucocytes polymorphonuclear neutrophils (PMN) and human umbilical vein endothelial cells (HUVEC), proinflammatory cytokines such as tumour necrosis factor alpha (TNF‐α) and interleukin‐6 (IL‐6) and soluble cellular adhesion molecules (CAMs) including E‐selectin, vascular cell adhesion molecule‐1 (VCAM‐1) and intercellular adhesion molecule‐1 (ICAM‐1). Results Anorexia nervosa was related to a decrease in weight, body mass index, waist circumference, systolic blood pressure, glucose, insulin and HOMA‐IR, and an increase in HDL cholesterol. These effects disappeared after adjusting for BMI. Anorexia nervosa induced a decrease in PMN rolling velocity and an increase in PMN rolling flux and PMN adhesion. Increases in IL‐6 and TNF‐α and adhesion molecule VCAM‐1 were also observed. Conclusions This study supports the hypothesis of an association between anorexia nervosa, inflammation and the induction of leucocyte–endothelium interactions. These findings may explain, in part at least, the increased risk of vascular disease among patients with anorexia nervosa.